Systematic Review of Prognostic Gene Signature in Gastric Cancer Patients - Xie, Longxiang; Cai, Linghao; Wang, Fei; Zhang, Lu; Wang, Qiang; Guo, Xiangqian (Frontiers in Bioengineering and Biotechnology, 2020)
Gastric cancer (GC) is one of the leading causes of cancer-related death in many countries. Recent studies have demonstrated that the gene signature derived from one or more genes can predict long-term outcomes in patients with GC. Here, by performing a comprehensive search in PubMed, we provided an up-to-date summary of 21 prognostic gene signatures for GC patients, and described the processing procedure of the selection, calculation and construction of gene signature. We also reviewed current web tools including PROGgene and SurvExpress that can be used to analyze the prognostic value of multiple genes for GCs. This review will aid in comprehensive understanding of the current prognostic gene signatures to accurately predict the outcome of GC patients, and may guide the future clinical management when the reliability of these signatures is validated in clinics.